2019
DOI: 10.1016/j.cegh.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of subgroup analyses in systematic reviews: A tutorial

Abstract: Authors of systematic reviews may perform subgroup analyses to investigate how treatment effect varies across different subgroups of patients or trials. Previous research has shown that Cochrane review authors do not sufficiently report their interpretation of subgroup analyses. Consequently, we developed a tutorial with the aim of improving the interpretation of subgroup analyses in reviews. We explain the importance of interpreting subgroup analyses, and demonstrate how to interpret subgroup analyses using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
222
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(224 citation statements)
references
References 5 publications
0
222
1
1
Order By: Relevance
“…The results of the subgroup analysis are shown in Table . In the subgroup analysis, a covariate was considered a source of heterogeneity when the two split subsets had no statistical heterogeneity, as indicated by a P ‐value greater than 0.05, and when both the I 2 values of the two split subsets moderately to significantly decreased compared to that of the general analysis . While overall heterogeneity existed ( P = 0.013, I 2 = 72%), we found that lesion size ( P = 0.076, I 2 = 47%, for subgroup <50 mm, P = 0.498, I 2 = 0, for subgroup ≥50 mm), number of included lesions in the studies ( P = 0.09, I 2 = 41%, for subgroup <90, P = 0.092, I 2 = 41%, for subgroup ≥90), and blinding to the reference standard when performing the index test ( P = 0.062, I 2 = 52%, for subgroup yes, P = 0.221, I 2 = 0, for subgroup unclear) may be the sources of heterogeneity for the ADC value in discriminating poorly differentiated HCCs.…”
Section: Resultsmentioning
confidence: 76%
“…The results of the subgroup analysis are shown in Table . In the subgroup analysis, a covariate was considered a source of heterogeneity when the two split subsets had no statistical heterogeneity, as indicated by a P ‐value greater than 0.05, and when both the I 2 values of the two split subsets moderately to significantly decreased compared to that of the general analysis . While overall heterogeneity existed ( P = 0.013, I 2 = 72%), we found that lesion size ( P = 0.076, I 2 = 47%, for subgroup <50 mm, P = 0.498, I 2 = 0, for subgroup ≥50 mm), number of included lesions in the studies ( P = 0.09, I 2 = 41%, for subgroup <90, P = 0.092, I 2 = 41%, for subgroup ≥90), and blinding to the reference standard when performing the index test ( P = 0.062, I 2 = 52%, for subgroup yes, P = 0.221, I 2 = 0, for subgroup unclear) may be the sources of heterogeneity for the ADC value in discriminating poorly differentiated HCCs.…”
Section: Resultsmentioning
confidence: 76%
“…A number of subgroup analyses were conducted to investigate whether factors such as dose, geographical location, in/outpatient settings, or aetiology modify the treatment effect. Overall, while some of the analyses revealed a significant subgroup effect ( P < 0.1 indicating a statistically significant subgroup effect), high heterogeneity between findings within each group and/or the small number of trials and participants contributing to each subgroup resulted in uncertainty as to whether these subgroup differences matter. Another limitation is that the definitions of diarrhoea and the inclusion criteria, such as the duration of symptoms prior to the inclusion, differed.…”
Section: Discussionmentioning
confidence: 96%
“…A number of subgroup analyses were conducted to investigate whether factors such as dose, country's Human Development Index, setting or aetiology modify the treatment effect. Overall, while some of the analyses revealed a significant subgroup effect, high heterogeneity between findings within each group and/or the small number of trials and participants contributing to each subgroup resulted in uncertainty as to whether these subgroup differences matter.…”
Section: Discussionmentioning
confidence: 97%